Effect of time of harvest on sorghum grain mold - and B.P. KURUNDKAR, SUNITA J. MAGAR (Indian Phytopathology, 2005)
Twelve sorghum genotypes were evaluated for grain mold intensity harvested at physiological maturity, maturity and delayed maturity in the field. Per cent moldy grains in each genotype at these three different stages were worked out after threshing of grains. Results indicated that minimum grain mold intensity was observed when harvesting was carried out at physiological maturity followed by maturity and delayed harvesting. Sorghum genotypes differed significantly for grain mold intensity in threshed grains. In field, grain mold intensity was less in genotypes Is 8545, ICSV 91008, CS 3541 and ICSV 95001 as compared to other genotypes. Per cent moldy grains in threshed grains were less in IS 8545, IS 18522 and ICSV 91008.